2001
DOI: 10.1038/sj.bjp.0704320
|View full text |Cite
|
Sign up to set email alerts
|

Clonidine‐induced nitric oxide‐dependent vasorelaxation mediated by endothelial α2‐adrenoceptor activation

Abstract: 1 To assess the involvement of endothelial a 2 -adrenoceptors in the clonidine-induced vasodilatation, the mesenteric artery of Sprague Dawley rats was cannulated and perfused with Tyrode solution (2 ml min 71 ). We measured perfusion pressure, nitric oxide (NO) in the perfusate using chemiluminescence, and tissue cyclic GMP by RIA. 2 In phenylephrine-precontracted mesenteries, clonidine elicited concentration-dependent vasodilatations associated to a rise in luminal NO. One hundred nM rauwolscine or 100 mM L … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
1
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 30 publications
1
71
1
4
Order By: Relevance
“…28,60 The α 2 -agonist clonidine may also be particularly effective due to a combination of spinal analgesic and local vasodilatory effects. 20,25 We have previously shown that the I-R injury associated with CPIP produces persistent tissue ischemia, indicated by reduced muscle perfusion, 38 as well as vasoconstrictor hyper-responsiveness, indicated by an enhanced reduction in hind paw blood flow after close arterial injection of NE. 78 The results here are consistent with a vasoactive role for NE from sympathetic efferents, in which activity at α 1 -receptors is pronociceptive due to vasoconstriction in already ischemic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…28,60 The α 2 -agonist clonidine may also be particularly effective due to a combination of spinal analgesic and local vasodilatory effects. 20,25 We have previously shown that the I-R injury associated with CPIP produces persistent tissue ischemia, indicated by reduced muscle perfusion, 38 as well as vasoconstrictor hyper-responsiveness, indicated by an enhanced reduction in hind paw blood flow after close arterial injection of NE. 78 The results here are consistent with a vasoactive role for NE from sympathetic efferents, in which activity at α 1 -receptors is pronociceptive due to vasoconstriction in already ischemic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The receptor suppresses its own adrenaline release from the terminal reticulum to the effecter including brain system, vasculature, and the heart, achieving sedation, analgesia, decreased BP, and bradycardia. Receptors in the peripheral vasculature control vessel tone in a contradictory fashion: vasoconstriction, 8-10 vasorelaxation, 11 and modifying each other. 12 Shimizu et al reported that medetomidine, a selective α-2 AR agonist, modifies the cardiac autonomic state not only by suppressing cardiac noradrenaline release but also by activating vagal acetylcholine release.…”
Section: Discussionmentioning
confidence: 99%
“…The possible involvement of NO-dependent mechanisms in the responses induced by clonidine and rilmenidine (a 2 -adrenoceptor/imidazoline receptor agonists), administered centrally or peripherally, has been proposed by several authors (Soares de Moura et al, 2000;Dobrucki et al, 2001;Figueroa et al, 2001;Sy et al, 2001;2002). Dobrucki et al (2001) showed that the a 2 -adrenoceptor/imidazoline receptor agonist clonidine, injected into the rat LV, decreased MAP and HR and simultaneously increased NO release in the NTS, and that blockade of NOS activity by injection of the NOS inhibitor N G -nitro-L-arginine-methyl ester (L-NAME) into the LV abolished these effects of clonidine.…”
Section: Introductionmentioning
confidence: 99%